RICE IMPORT AND INDONESIA'S COMMITMENT TO FREE TRADE COOPERATION (2018-2023) - Tety Rachmawati; Rahayu Lestari; Ayu Puspitasari (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The high demand for rice in Indonesia is not matched by adequate rice stocks. Coupled with high production costs, the government tends to prefer importing rice to meet domestic demand. Various agreements have been made with trading partners to meet domestic rice supply. Indonesia has entered into various rice trade agreements with its five main trading partners. However, imports do not necessarily solve the problems in Indonesia's rice supply chain. This study aims to analyze the impact of rice import cooperation on food sovereignty in Indonesia. This is a qualitative study with an emphasis on a case study approach. Data was obtained through a literature study from various primary and secondary sources. The results of the study show that Indonesia's rice import cooperation with trading partner countries is a mutually beneficial cooperation. This cooperation is Indonesia's commitment to free trade under the WTO agreement.